Uterovaginal prolapse with multiple Vesical calculi: A rare case report (Journal of Dhaka Medical College, 2017)
Uterine prolase is a common gynaecological disease .It is usually associated with cystocele and or rectocele as well as enterocele. Recurrent urinary tract infections may occur in chronically unreduced cystocele leading to calculus formation,cystitis,pyelitis,pyelonephritis and renal failure.We report a case of a 70 years old multiparous lady with third degree uterovaginal prolapse for twenty years, presence of multiple vesical calculus in the cystocele was noted on X-ray pelvis while undergoing investigation.Suprapubic cystolithotomy followed by vaginal hysterectomy with pelvic floor repair was done. Multiple vesical calculus were removed. Postoperative course was uneventful and she was discharged on 10th post-operative day. Patient is still on follow up with good urinary function and no recurrent UTI.J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 77-79